Participants in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a group of men, women and children participating in the 1986 y-Walk. They are photographed from behind and are walking down South Market Street in downtown San Jose across from the Plaza. Some of them are carrying balloons. The construction for the Fairmont Hotel is just barely visible ahead of the walkers, and they have passed the "United Food and Commercial Worke[rs]. Local 428, AFL-CIO" building.